Rapid and Repeatable Self‐Healing Superoleophobic Porous Aluminum Surface Using Infiltrated Liquid Healing Agent. Issue 19 (15th July 2018) - Nakayama, Katsutoshi; Koyama, Akira; Zhu, Chunyu; Aoki, Yoshitaka; Habazaki, Hiroki
Abstract: This paper reports rapid self‐healing on superoleophobic hierarchically porous aluminum surfaces within 1 h even at room temperature. This self‐healing surface is prepared by infiltration of a liquid fluoroalkylsilane (FAS) coating into the substrate pores. The FAS‐infiltrated dual‐pore superoleophobic surface becomes superoleophilic after oxygen plasma treatment due to the damage done to the organic coating. However, the superoleophobicity is completely recovered by exposure to normal atmosphere at room temperature, and this rapid self‐healing is repeatable. The FAS liquid appears to coat the nanopore walls, rather than filling the nanopores. The high wettability of FAS on surfaces induces the rapid recoating of the plasma‐damaged surface, contributing to the self‐healing of the superoleophobicity. Abstract : Rapid and repeatable self‐healing of superoleophobic surfaces is fabricated in this study by infiltration of fluoroalkylsilane liquid, which acts as a healing agent of organic monolayer coating, in nanopore channels of hierarchical mico‐/nanopore surface. The hierarchical porous structure is developed by industrially applicable chemical etching and anodizing of aluminum metal.